Investigating the dynamics of volatile sulfur compound emission from primary systems at a water resource recovery facility. (6th August 2020) - Bazemo, Ulrich; Gardner, Elena; Romero, Adrian; Hauduc, Helene; Al‐Omari, Ahmed; Takacs, Imre; Murthy, Sudhir; Torrents, Alba; De Clippeleir, Haydée
Abstract: This study quantifies volatile sulfur compound (VSC) emissions from primary settling tanks and investigates their mechanisms of generation. Hydrogen sulfide (H2 S) and methyl mercaptan (MM) concentrations in the off‐gas were dominant among the VSCs analyzed, while dimethyl sulfide (DMS) and dimethyl disulfide (DMDS) were under their odor threshold for most sampling dates. H2 S emission in primary settling tanks was mainly the result of the stripping of dissolved sulfide (64%) generated in the sewers. Results indicate that MM emission was more dependent on the conditions in the primary clarifiers (only 16% stripping). Prevention of odor emission in primary settling tanks can be achieved by managing biofilms and microbial reactions in the sewer network. Controlling the biomass seeding and fermentation product availability in the primary settling tanks is essential to significantly minimize the kinetics of H2 S and MM generation. Overall, the management of sludge blanket heights and thus avoiding time at low oxidation–reduction potential minimized odor emission independent of sewer conditions. Practitioner points: H2 S emission from primary clarifiers mainly originated from the stripping of the dissolved sulfide formed in the sewers. MM emission contributed for 89% to overall odor emitted from primary clarifiers. Seeding of active biomass from the sewer into the primary clarifiers was be the main driver for both MM and H2 S formation. Increased availability of fermentation products or fermenters increased MM production. Abstract : Interactions and impacts of MM and H2S formation in sewer network on primary clarification emissions